Complete chloroplast genome sequence of Hanabusaya asiatica (Campanulaceae), an endemic genus to Korea. (3rd May 2016) - Cheon, Kyeong-Sik; Yoo, Ki-Oug
Abstract: The complete chloroplast genome of Hanabusaya asiatica, an endemic genus to Korea, was determined in this study. The total genome size was 167, 287 bp in length, containing a pair of inverted repeats (IRs) of 26, 877 bp, which were separated by large single copy (LSC) and small single copy (SSC) of 104, 955 and 8578, respectively. The overall GC contents of the plastid genome were 38.8%. One hundred and twelve unique genes were annotated, including 78 protein coding genes, 30 tRNA genes and 4 rRNA genes. In these genes, 17 genes contained 1 intron, and 2 genes comprised of 2 introns.